REACTION OF ISONIAZID (INH) WITH RHENIUM (Re) USING DIFFERENT REDUCING AGENTS, CHARACTERIZATION OF COMPLEXES AND X-RAY CRYSTAL STRUCTURE OF INH DIMER - Amir, N.; Roohi, S.; Pervez, S.; Jehangir, M.; Miyashita, Y. (The Nucleus, 2020)
Reactivity of INH with NH4ReO4 was studied using SnCl2•2H2O and NaBH4 as reducing agents. 99mTc labelled INH was also prepared according to the reported procedure for comparison. A complex (1) similar to 99mTc-INH (2) was formed with NH4ReO4 in the presence of SnCl2•2H2O. On the other hand, NaBH4 gave a dimer of INH (3) which was confirmed by x-ray crystallography. The products, 1, 2 and 3 were characterized by HPLC, IR spectra and x-ray crystallography.